«¿16 céntimos a cambio de aguas ácidas?». Respuestas políticas a la expansión minera en Cajamarca - Zavaleta, Mauricio (2019)
For decades, Cajamarca has housed one of the most productive gold mines in the world. Between 1992, when the operations of the Yanacocha deposits began, until 2011, when the most important expansion project of the operating company was suspended, extractive activities have been a source of controversy. Only between 2004 and 2011 three conflicts reached national relevance in Cajamarca: Quilish (2004), Combayo (2006) and Minas Conga (2011). This continuum allows analyzing different types of «responses» —especially from rural areas— to mining. The article proposes that the peasant responses have been oriented to the negotiation of benefits that compensate the affectation of natural resources and allow the localities to accede, albeit in an indirect and limited way, to the profits produced by the industry. However, when the agreements reached with the company are not met or the population perceives that the impact on the means of subsistence is greater than the benefits received, incentives are generated for political mobilization. In this context, different coalitions had emerged between rural villages and urban organizations that, though ephemeral in organizational terms, promoted mobilizations against Yanacocha’s expansion projects with remarkable effectiveness.